Putting Education Back at the Center: Some Reflections and Proposals on the Italian Situation - Emanuela Susca (Mediterranean Journal of Social Sciences, 2023)
In this article, I address issues of inequality in Italy and, in particular, the role that education can play in fighting inequality. Moving beyond the nevertheless real problem of the scarcity of funds allocated by the Italian governments to education, I focus on the objectives that should inform spending criteria, thus emphasizing the importance of truly inclusive education, achievable through an ambitious path of comprehensive and incisive reforms. A country that does not excel in the civic sense and that for some scholars is even becoming less civilized, Italy should put education back at the center not only as a matter of social justice, but also to avert decline and improve the quality of its democratic coexistence. Received: 22 February 2023 / Accepted: 27 April 2023 / Published: 5 May 2023